Analysis of the Implementation of Article 22 Paragraph (2) of ATR/BPN Ministerial Regulation Number 6 of 2018 on Complete Systematic Land Registration (PTSL): Limitations and Challenges in Recording Proof of Community Land Ownership - Taufiq, Fida Nabilah; Masykur, M. Hamidi; Supriyadi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The problem of incomplete or non-existent land ownership proof among the community has arisen in one of the villages in Sidoarjo Regency. This is rooted in the registration of land through the Comprehensive Systematic Land Registration (PTSL) program by one of the heirs named "A". After the issuance of the certificate, other heirs raised objections regarding land ownership, leading to an unresolved dispute until now. This situation is not in line with the intended purpose of land registration, given that Indonesia has comprehensive regulations governing land matters, including dispute resolution. The persistent delay in resolving the dispute raises questions about whether there is a regulatory mismatch or implementation issues within the PTSL program. This research adopts a socio-legal research method with a socio-legal sociology approach and legal data collection techniques such as interviews, observations, and document analysis conducted at the Sidoarjo Regency ATR/BPN Office. The population includes employees of the ATR/BPN Office in Sidoarjo Regency, with samples selected purposively from the General and Personnel Substantive Group Coordinator or the PTSL Program committee or appointed officials. The research findings will be analyzed using descriptive legal data analysis. The results indicate that the implementation of the PTSL program aligns with existing regulations, despite encountering some obstacles. The identified challenges include disputes related to data forgery, conflicts among heirs, discrepancies in land measurement processes, and land occupation by individuals other than the direct owners. The ATR/BPN Office in Sidoarjo addresses these challenges by mediating disputes before PTSL registration to reach agreements. In cases where no consensus is reached, the registration process is postponed until a resolution is achieved between the parties. Additionally, in post-PTSL certificate issuance disputes, mediation is employed, and if no agreement is reached, the category may be downgraded from K2 to K1, or legal proceedings may be pursued to determine rightful ownership of the land parcel.